Compound Parabolic Tapered Fiber for Fiber Coupling with a Highly Divergent Source - Chen, Lee C.; Low, Andy L. Y.; Chien, Su Fong (Optica Publishing Group, 2004)
A novel fiber tapering shape, which is based on compound parabolic geometry, is proposed to increase the acceptance angle of a compound parabolic concentrator. The proposed design is described by use of ray optics on a step-index multimode fiber. (C) 2004 Optical Society of America.